Pembentukan Tubuh Perempuan Flores Dalam Tradisi Belis - Rodliyah, Siti (Universitas Veteran Bangun Nusantara Sukoharjo, 2022)
The Belis tradition has been carried out by the people of Flores since hundreds of years ago. The belis tradition is part of the customary law of marriage in the cultural area of the Flores community. The term belis can be matched with the meaning of a dowry or an award given by a male family to a female family for proposing to a woman who will then enter into a male family clan or tribe. This study aims to reveal the formation of the female body in the Belis tradition of the Flores community. The research method uses descriptive qualitative method with content analysis techniques. The result is that the tradition of giving belis is maintained as a guarantor of human reproduction. The belis tradition which later became the great narrative of the Flores culture, made it a very strong cultural logocentrism. Belis tradition can be said as a reaction to the doctrine that women have reproductive tasks like machines. In conclusion, it can be said that this belis tradition is also the background of the Flores woman's body. The female body becomes a metaphor for mapping social life to reflect reality. In the end, it is increasingly recognized that perception of the body is more a sociocultural construct.